The flowers of buffoonery - Dazai, Osamu 1909-1948 (A new directions paperbook, 2023)
"The Flowers of Buffoonery opens in a seaside sanitarium where Yozo Oba-the narrator of No Longer Human at a younger age-is being kept after a failed suicide attempt. While he is convalescing, his friends and family visit him, and other patients and nurses drift in and out of his room. Against this dispiriting backdrop, everyone tries to maintain a lighthearted, even clownish atmosphere: playing cards, smoking cigarettes, vying for attention, cracking jokes, and trying to make each other laugh. While No Longer Human delves into the darkest corners of human consciousness, The Flowers of Buffoonery pokes fun at these same emotions: the follies and hardships of youth, of love, and of self-hatred and depression. A glimpse into the lives of a group of outsiders in prewar Japan, The Flowers of Buffoonery is a darkly humorous and fresh addition to Osamu Dazai's masterful and intoxicating oeuvre"--